Gargling with Aloe vera extract is effective to prevent the Ventilator-Associated Pneumonia (VAP) - Mita Agustina (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Long-term use of a mechanic ventilator may cause Ventilator- Associated Pneumonia (VAP) infection, nosocomial pneumonia that occurs after 48 hours in patients using mechanical ventilation either through the endotracheal tube or the tracheostomy tube. To prevent the occurrence of VAP, antiseptic liquid (mouthwash) such as chlorhexidine 2% maybe recommended. However, gargling using chlorhexidine may also cause allergies, thus, Aloe vera extract could be an alternative. Aims: The purpose of this study was to determine the effectiveness of Aloe vera extract as mouthwash to prevent the occurrence of Ventilator-associated pneumonia. Methods: This research is a quasi-experiment case-control study with a pre- posttest control group design. The sample size in this study was 30 respondents who were equally distributed into two groups; intervention group was administered using Aloe vera extract, while chlorhexidine was practiced for the control group. To determine the occurrence of VAP, Clinical Pulmonary Infection Score (CPIS) for Ventilator-Associated Pneumonia was measured on the first day of intubation and the fourth day, enumerated by nurses in the emergency room. CPIS is a set of indicators comprised of temperature, leucocyte, trachea secretion, oxygenation (PaO2/FiO in mm Hg), and thorax photo. CPIS value below than five will be regarded non-VAP, while CPIS scored 6-9 will be diagnosed as VAP. Results: Oral hygiene with Aloe vera extract was able to prevent the occurrence of VAP (p-value = 0.001), but there was no significant difference between the control group and intervention in the CPIS component temperature, leukocytes, tracheal secretions, FiO2, and the thoracic component. Conclusions: Oral hygiene with Aloe vera extract effectively prevented the occurrence of V entilator-Associated Pneumonia (V AP) compared to chlorhexidine.